Heterogeneity of memory T cells in aging - Jain, Abhinav; Sturmlechner, Ines; Weyand, Cornelia M.; Goronzy, Jörg J. (Frontiers in Immunology, 2023)
Immune memory is a requisite and remarkable property of the immune system and is the biological foundation of the success of vaccinations in reducing morbidity from infectious diseases. Some vaccines and infections induce long-lasting protection, but immunity to other vaccines and particularly in older adults rarely persists over long time periods. Failed induction of an immune response and accelerated waning of immune memory both contribute to the immunocompromised state of the older population. Here we review how T cell memory is influenced by age. T cell memory is maintained by a dynamic population of T cells that are heterogeneous in their kinetic parameters under homeostatic condition and their function. Durability of T cell memory can be influenced not only by the loss of a clonal progeny, but also by broader changes in the composition of functional states and transition of T cells to a dysfunctional state. Genomewide single cell studies on total T cells have started to provide insights on the influence of age on cell heterogeneity over time. The most striking findings were a trend to progressive effector differentiation and the activation of pro-inflammatory pathways, including the emergence of CD4 + and CD8 + cytotoxic subsets. Genome-wide data on antigen-specific memory T cells are currently limited but can be expected to provide insights on how changes in T cell subset heterogeneity and transcriptome relate to durability of immune protection.